2020
DOI: 10.2196/17883
|View full text |Cite|
|
Sign up to set email alerts
|

Habit Strength, Medication Adherence, and Habit-Based Mobile Health Interventions Across Chronic Medical Conditions: Systematic Review

Abstract: Background Unintentional medication nonadherence is common and has been associated with poor health outcomes and increased health care costs. Earlier research demonstrated a relationship between habit strength and medication adherence. Previous research also examined a habit’s direct effect on adherence and how habit interacts with more conscious factors to influence or overrule them. However, the relationship between habit and adherence and the role of habit-based mobile health (mHealth) intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…Growing mobile phone ownership globally and integration with the internet [ 11 , 12 ] have prompted the development of and research into mobile health (mHealth) interventions to address a broad range of behavior change practices for chronic disease management. These mHealth tools seek to modify a range of broad and specific behavioral factors related to diet [ 13 ], exercise [ 14 ], and medication adherence [ 15 , 16 ] to manage a range of chronic conditions, including diabetes [ 17 , 18 ], obesity [ 19 , 20 ], and cardiovascular diseases [ 15 ]. A variety of mHealth interventions have shown promising results in a variety of populations across the lifespan [ 21 , 22 ] and have particularly provided equitable support to remote, regional, and underserved populations [ 23 - 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing mobile phone ownership globally and integration with the internet [ 11 , 12 ] have prompted the development of and research into mobile health (mHealth) interventions to address a broad range of behavior change practices for chronic disease management. These mHealth tools seek to modify a range of broad and specific behavioral factors related to diet [ 13 ], exercise [ 14 ], and medication adherence [ 15 , 16 ] to manage a range of chronic conditions, including diabetes [ 17 , 18 ], obesity [ 19 , 20 ], and cardiovascular diseases [ 15 ]. A variety of mHealth interventions have shown promising results in a variety of populations across the lifespan [ 21 , 22 ] and have particularly provided equitable support to remote, regional, and underserved populations [ 23 - 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…As described in the Adherence Standard, 6 assessing adherence more regularly may ultimately serve an important interventional role, potentially by way of providing a reminder, increasing accountability and self‐monitoring skills, and promoting healthy habits. Notably, habit strength is positively correlated with medication adherence—if daily adherence surveys promote more automatic behavior, there may be less chance for an AYA to forget to take their medication over time 43 . While medication reminders are prone to habituation, 44–46 providing a two‐way reminder (ie, asking whether or not the patient took the dose) may be more engaging.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, habit strength is positively correlated with medication adherence-if daily adherence surveys promote more automatic behavior, there may be less chance for an AYA to forget to take their medication over time 43. While medication reminders are prone to habituation,[44][45][46] providing a two-way reminder (ie, asking whether or not the patient took the dose) may be more engaging.…”
mentioning
confidence: 99%
“…Various factors govern drug adherence, including delivery of health care services, economic situation, and cultural factors of patients [28]. Behavioral factors like forgetfulness, inappropriate time management, lack of awareness of disease, and fear of drugs pose additional barriers to drug adherence [29][30][31]. It has been observed that parents of patients with SCD with mild symptoms are less willing to accept the risk associated with taking hydroxyurea, particularly with regard to the long-term side effects, which include birth defects and cancer [29].…”
Section: Sickle Cell Disease: a Life-threatening And Highly Morbid Disordermentioning
confidence: 99%